ANALISIS PENGARUH LOCUS OF CONTROL, NEED FOR ACHIEVEMENT DAN RISK TAKING TERHADAP INTENSI BERWIRAUSAHA ALUMNI MAHASISWA JURUSAN AKUNTANSI POLITEKNIK NEGERI MEDAN - Cut Nizma; Dina Arfianti Siregar (Politeknik Negeri Lhokseumawe, 2018)
Abstract : The purpose of this research is to know and analyze the influence of Locus of Control, Need for Achievement and Risk Taking Against Intellect entrepreneurship Alumni Students Accounting Department Politeknik Negeri Medan. The theory used is the theory of human resource management and entrepreneurship related to Locus of Control, Need for Achievement, Risk Taking and Intensi Entrepreneurship. The type of this research is descriptive quantitative and the nature of the research is explanatory. The number of samples used is 98 respondents. This research use accidental sampling method. Data analysis using multiple linear regression model. The results showed that the variables of Locus of Control, Need for Achievement and Risk Taking simultaneously affect the Intensi Entrepreneurship students majoring in Accounting Politeknik Negeri Medan. Partially, Locus of Control, Need for Achievement and Risk Taking variables significantly influence the Intensi Entrepreneurship students majoring in Accounting Politeknik Negeri Medan and the most dominant variable affecting entrepreneurial interest is Risk Taking variable. Keywords: Locus of Control, Need for Achievement, Risk Taking, Intensi Entrepreneurship